2013
DOI: 10.1111/jog.12273
|View full text |Cite
|
Sign up to set email alerts
|

Value of maternal procalcitonin levels for predicting subclinical intra‐amniotic infection in preterm premature rupture of membranes

Abstract: ProCT levels were significantly higher in patients with PPROM, and facilitate identification of those who require expectant management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 26 publications
4
45
0
Order By: Relevance
“…In addition, recent studies have shown that procalcitonin is more sensitive and specific than CRP in the early detection of bacterial infection among infants and neonates. However, there are limited studies on the prediction of early onset neonatal sepsis (EONS) with maternal blood procalcitonin level [12] . It was hypothesized that maternal blood procalcitonin concentrations are upregulated in pregnancies complicated with PPROM before the occurrence of clinical CA and neonatal infection.…”
mentioning
confidence: 99%
“…In addition, recent studies have shown that procalcitonin is more sensitive and specific than CRP in the early detection of bacterial infection among infants and neonates. However, there are limited studies on the prediction of early onset neonatal sepsis (EONS) with maternal blood procalcitonin level [12] . It was hypothesized that maternal blood procalcitonin concentrations are upregulated in pregnancies complicated with PPROM before the occurrence of clinical CA and neonatal infection.…”
mentioning
confidence: 99%
“…Oludaq et al showed that the maternal serum level of PCT in women with PPROM who also had histologic chorioamnionitis was significantly higher than the maternal serum level of PCT in women with PPROM who did not have chorioamnionitis. Moreover, the sensitivity and specificity of PCT were 92.3% and 68.4%, respectively, at 0.054 ng/ml serum level for the diagnosis of chorioamnionitis (17).…”
Section: Discussionmentioning
confidence: 99%
“…Serum levels of PCT higher than 0.06 ng/ml were considered an increased amount. This amount was selected because of the use of different cutoff points in the reviewed articles, the population proximity of the neighboring country, Turkey, to Iran, and the novelty of our study (8,17). A cobas e411 analyzer and a Roche diagnostic kit (Lot 187-424-02) were used to measure the level of PCT.…”
Section: Laminating With Entellan Merckmentioning
confidence: 99%
“…Once the infection is under control and the patient's condition has improved, the PCT concentration drops. Recently, the PCT concentration has been widely used as a standard for bacterial infection detection and as a guideline for antibiotic use (8)(9)(10). Studies have shown that both CRP and PCT have high sensitivities and specificities in PROM associated with intrauterine infection.…”
Section: Introductionmentioning
confidence: 99%
“…They can be used to predict asymptomatic intrauterine infection. However, the results have great discrepancy in different studies (5)(6)(7)(8)(9)(10). To further investigates the clinical application value of PCT and CRP in the early prediction and diagnosis of subclinical intrauterine infection in patients with premature rupture of membranes (PROM), A retrospective analysis was performed based on 276 patients with PROM during pregnancy that were admitted into our hospital between January 2011 and January 2016.…”
Section: Introductionmentioning
confidence: 99%